ANALISIS PASAL 41 HINGGA PASAL 46 PERDA KOTA BUKITTINGGI NOMOR 02 TAHUN 2024 TENTANG KETENTRAMAN KETERTIBAN UMUM(STUDI TAFSIR MAQASHIDI DAN AL-QUR'AN) - Chandra Kirana; Muhammad Taufiq (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
The rise of social disease, namely sexual deviation, which occurs in the city of Bukittinggi, is a major factor in the city of Bukittinggi, where the philosophy of life of the Minangkabau people, especially the city of Bukittinggi, is "Adat basandi syara', syara' basandi Kitabullah". This research aims to analyze articles 41 to 46 concerning administrative sanctions for those who commit deviant acts such as sexual deviation and other immoral acts and the purpose of establishing these regulations. This type of research is field research, where the main data used is obtained from the field, in this case the authorities and authorities over the implementation of the Bukittinggi City regional regulations and the perpetrators of immorality themselves. This research uses a qualitative approach, namely a method with a research process based on perceptions of a phenomenon with a data approach that produces descriptive analysis in the form of verbal and written sentences from the research object. The results of this research are that the Bukittinggi City Regional Regulations in Articles 41 to Article 46 aim to protect the public from deviant sexual behavior and potentially damaging pornographic content. As stated in the Al-Quran, Surah Al-Isra' verse 32, which prohibits someone from committing adultery. With this regulation, people can heed it and create a good and peaceful environment. Based on maqashidi interpretations and the Koran in general, it emphasizes the importance of maintaining morality and public order.